ضبط النشاط الصيدلاني في التشريع الجزائري - محمادي جيهان (جامعة المسيلة, 2025)
This dissertation examines the regulation of pharmaceutical activity in Algerian legislation, focusing on the sector's transition from a state-run monopoly model to a regulatory framework based on oversight mechanisms within a market economy. The central research question explores the extent to which the Algerian legislator has succeeded in establishing an effective legal and institutional framework that ensures the proper regulation of pharmaceutical products and safeguards public health. The study is structured into two chapters: the first addresses the newly established regulatory actors, most notably the National Agency for Pharmaceutical Products, with its extensive organizational and supervisory powers; the second explores the classical actors, such as the Ministry of Health and the General Pharmaceutical Inspectorate. The findings reveal that, despite notable progress, the current system still requires stronger inter-institutional coordination, legal unification, and modernization of control mechanisms to ensure effective regulation of this vital sector.
Keywords: Pharmaceutical activity; Regulation of emerging actors; Classical actors; Institutional framework; Legal framework; Monitoring.